To what extent should hospital be design for expected emergency and preparedness to manage unforseen disaster: sharing hospital design experiences as case study - Mohd Arin, Nabihah; Mohd Nawawi, Norwina; Aripin, Srazali (2019)
Malaysian Government hospital emergency departments (EDs) has shown a steady increase in patients’ attendance for many types of emergencies. The designs of existing Emergency departments are to meet the services as stipulated by the Ministry of Health, Malaysia (MOH) according to the level of care. The current concern is the ability of the hospital emergency departments to provide adequate medical treatment with existing facilities when there is a surge capacity for earthquake-related disaster occurrence. The recent earthquake in 2015 and 2018 shows that Malaysia is no longer safe from such natural disasters. Hence, there is a need to review current provisions in existing emergency departments, especially in the state of Sabah to be more earthquake disaster-ready. A qualitative methodology was adopted using literature review and case studies. This paper surveyed existing hospital emergency services and facilities provided in the earthquake-prone areas of Sabah to identify the adequateness of services and facilities in Sabah’s local hospitals in meeting the surge capacity. For this paper, the study focuses on identifying the adequacy of existing services and facilities, including the building structure of the EDs to meet the surging demand from the earthquake disaster. The significant of the research contribute to the recommendation of improvements to existing and new Eds in earthquake-prone areas.